The Frenzy Of Orlando - Yap, Wei Ying (Nanyang Technological University, 2022)
‘The Frenzy of Orlando’ is an illustration project that reimagines the epic poem, ‘Orlando Furioso’. Since the publication of this project in April, it seeks to demonstrate a modern approach to providing appealing visuals to enhance reading experiences – a means to step away from conventional representations illustrated by Gustave Dore, the same 18th-century illustrator responsible for illustrating 13th-century’s The Divine Comedy by Dante Alighieri. Essentially, contemporary readers could understand and differentiate the descriptive narrative easily. This project aimed to highlight the main scenarios discussed in each canto, which is a division of sections within a long poem or simply a chapter to produce corresponding visuals as a summarizing element. To top it off, the style language of this modern version would adopt the artistic techniques created by Ronald Searle (1920-2011) that add a whimsical overlay to the epic’s narrative tone.